2021
DOI: 10.1097/shk.0000000000001783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Evidence, Pharmacology, and Interplay of Fluid Resuscitation and Vasoactive Therapy in Sepsis and Septic Shock

Abstract: We sought to review the pharmacology of vasoactive therapy and fluid administration in sepsis and septic shock, with specific insight into the physiologic interplay of these agents. A PubMed/MEDLINE search was conducted using the following terms (vasopressor OR vasoactive OR inotrope) AND (crystalloid OR colloid OR fluid) AND (sepsis) AND (shock OR septic shock) from 1965 to October 2020. A total of 1,022 citations were reviewed with only relevant clinical data extracted. While physiologic rationale provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…However, norepinephrine weaning in septic shock is not simply the reverse of the acute phase management. In the acute phase, it has been shown that the cardiovascular equilibrium depends on the underlying disease (i.e., sepsis vs. non sepsis), the type and dose of medications (inotrope, vasopressor, or both), and the fluid therapy provided during the resuscitation phase ( 1 , 11 , 13 , 19 21 ). Several studies have demonstrated that norepinephrine can act as a fluid challenge by increasing venous return and cardiac pre-load ( 8 , 9 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, norepinephrine weaning in septic shock is not simply the reverse of the acute phase management. In the acute phase, it has been shown that the cardiovascular equilibrium depends on the underlying disease (i.e., sepsis vs. non sepsis), the type and dose of medications (inotrope, vasopressor, or both), and the fluid therapy provided during the resuscitation phase ( 1 , 11 , 13 , 19 21 ). Several studies have demonstrated that norepinephrine can act as a fluid challenge by increasing venous return and cardiac pre-load ( 8 , 9 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in blood pressure may be explained by the effects of norepinephrine on cardiac function and arterial load ( 6 , 12 , 19 , 20 ). We did observe a decrease in CFI and ventricular elastance, which are two parameters of cardiac systolic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncertain whether restricted i.v. fluid volume and timing of initiation of vasopressor support in adult septic shock patients can reduce mortality and organ dysfunction, and whether the strategy is feasible (11). Currently, there is a lack of clinical evidence and no recommendation in relevant guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…We finish up the October issue of SHOCK with a detailed review about fluid resuscitation and vasoactive therapy in sepsis and septic shock. Barlow and Bissell (20) team up to provide an evaluation of evidence and pharmacology of vasoactive therapy and fluid administration in sepsis and septic shock, with specific insight into the physiologic interplay of these agents. A total of 1,022 citations were reviewed with only relevant clinical data extracted.…”
mentioning
confidence: 99%